Detection of scour depth using singlemode-multimode-singlemode fiber sensor / Norshazmira Mat Azmi - Norshazmira, Mat Azmi (2018)
This thesis presents an experimental study in the laboratory to develop and test a method for continuously measuring and monitoring scour using Single mode-Multimode-Singlemode (SMS) sensor. The study provides an insight into the SMS technology and develops the framework using this technology to eventually address central theme in river mechanics and sediment transport; which is the scour/deposition depth around a hydraulic structure. In particular, this study develops a new packaging method for the sensor to detect the extent of local scour where a set of experiments are performed using hydraulic flume for a duration of 900 minutes with a maximum scour depth of 27 mm. The experiments presented herein are classified into two main groups, (1) the laboratory work to develop the sensor package and (2) the wavelength shift vs. the scour depth experiments. The laboratory results show that the sensor has a potential to be applied in a real-time monitoring application such as in bridge scouring. Wavelength shifts of 0.12 nm and 0.06 nm are observed at the transitions between different phases in the development of local scour around PVC pipe.